Caricom's trade : a quick reference to some summary data : 1985-1992 (CCS GeorgetownGY, 1994)
Presents data on CARICOM's total trade with prinicipal trading partners and the rest of the world; as well as, CARICOM's trade with respective trading partners including intra-CARICOM trade.
DC